Combining additive manufacturing and catalysis: a review. Issue 16 (6th July 2017) - Hurt, C.; Brandt, M.; Priya, S. S.; Bhatelia, T.; Patel, J.; Selvakannan, PR.; Bhargava, S.
Abstract : A review on additive manufacturing (AM) applied to heterogeneous catalysis reveals enabling power of AM and challenges to overcome in chemical interfacing and material printability. Abstract : This review presents an insight into additive manufacturing (AM) technologies as they are applied to heterogeneous catalysis; the combination of these fields presents opportunities but also comes with challenges. AM enables greater design complexity, rapid prototyping, control over reactant stoichiometry and unique catalyst immobilisation options. The challenges to applying AM in heterogeneous catalysis are associated with limited material choices, quasi-stable printed materials and chemical interfacing of the catalyst system with cthese printed materials. AM printing technologies are introduced to the heterogeneous catalysis research community with a focus on the many benefits they offer in this growing field.